Determinants of stock returns: Evidence from Egypt - El Abd, Reem Abd El Maksoud Ahmed (AUC Knowledge Fountain, 2016)
This paper aims at identifying the determinants of stock returns in the Egyptian stock market. It does so by means of applying four different asset pricing models to the Egyptian stock returns: the CAPM, Fama-French three-factor model, Carhart four-factor model, and Fama-French five-factor model. The main findings of this thesis are that there is a significant size effect in the Egyptian stock returns, but there is no evidence of the presence of value or momentum effects. The results for operating profitability and investment are mixed therefore they need to be investigated further. Also, this paper provides evidence of the superiority of Fama-French five-factor model relative to the other asset pricing models tested.